2014
DOI: 10.2332/allergolint.14-oa-0700
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Characteristics That Differentiate Hereditary Angioedema in 72 Patients with Angioedema

Abstract: Early onset of AE, positive family history, recurrent AE in the extremities and GI tract, and suffocation are distinctive characteristics of HAE. A low serum level of C4 is a useful marker for making a differential diagnosis of HAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
1
20
1
2
Order By: Relevance
“…However, the second measurement during an attack exhibited a low C4 level. 5 Therefore, normal C4 levels in the present cases may be attributable to the lack of the attacks of angioedema so far. Thus, although it has been generally agreed that low serum levels of C4 are a useful marker for HAE, normal serum C4 levels do not exclude the possibility of HAE.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…However, the second measurement during an attack exhibited a low C4 level. 5 Therefore, normal C4 levels in the present cases may be attributable to the lack of the attacks of angioedema so far. Thus, although it has been generally agreed that low serum levels of C4 are a useful marker for HAE, normal serum C4 levels do not exclude the possibility of HAE.…”
mentioning
confidence: 55%
“…According to Ohsawa et al, 5 the sensitivity and specificity of low C4 for HAE were 95.6% and 93.8%, respectively. In Ohsawa et al's case series, only one of 23 HAE patients showed a normal level of C4.…”
mentioning
confidence: 92%
“…Although C1‐INH has been demonstrated to be safe and effective, self‐administration and LTP are not licensed, and accessibility to treatment is challenging for many patients in Japan . In addition, awareness of HAE among physicians in Japan is low and the limited availability of effective therapies increases the burden of HAE . Diagnosis of HAE worldwide can take an average of 8.3 years; this figure is thought to be much longer in Japan .…”
Section: Discussionmentioning
confidence: 99%
“…73 Diagnosis of HAE worldwide can take an average of 8.3 years; this figure is thought to be much longer in Japan. 29,73,74 While danazol is available for off-label use, it has been associated with numerous side effects, including virilization, headaches, depression, and acne. In addition, the risk of adverse events in response to androgens increases the longer the duration of treatment.…”
Section: Conclusion Smentioning
confidence: 99%
“…Elevated levels of bradykinin due to activated kallikrein and factor XII are considered to increase the vascular permeability in HAE (8). In contrast to ACE-I-induced angioedema where most of laboratory tests are normal, including complement, HAE can be diagnosed by the decreased levels of complement C4 and C1-INH activity (9). The guidelines for HAE diagnosis and treatment in Japan are noted in reference 10 (10).…”
mentioning
confidence: 99%